Perawatan Kolaborasi untuk Kesehatan Mental Perinatal: Tinjauan Literatur: Collaborative Care for Perinatal Mental Health: Literature Review - Hertati, Dessy; Mujahadatuljannah, Mujahadatuljannah; Rabiatunnisa, Rabiatunnisa; Setyoningsih, Dewi; Nurhidayati, Evi (Jurnal Surya Medika (JSM), 2022)
Factors that enhance women’s experience in health care during the perinatal period are providing opportunities to develop interrelated relationships with professional health care. The services provided are high-quality information for women, families, and health professionals. Collaborative practice can also reduce complications, hospital care, health team conflicts, and mortality rates. General patients report higher satisfaction, better service, and better health outcomes. In the health sector, collaborative practice can improve patient and health team satisfaction, reduce the duration of care, reduce maintenance costs, reduce the incidence of self-defense, and reduce outpatient visits. Objective: The literature of this review is to summarize collaborative care for perinatal mental health. Method: This study is a journal publication with a literature summary, and article search using comparative studies of computerized databases (PubMed and BMC). Results: In improving mental health care services Collaboration between health care institutions, general practitioners, and mental health professional services is needed. Access to mental health care is inadequate, this is because perinatal health care providers are not sufficient to make initial preparations, referrals, complaints about aspects of maternal emotional care, and psychological services only benefit a portion of the population. Conclusion: The main problem of this collaboration is the knowledge of doctors and general nurses on perinatal maternal mental health problems, poor supervision systems, inadequate information systems, and clinical technology. Collaboration between professionals in the health and health sector as well as adequate health program policy support, as well as increasing shared awareness will improve mental health for mothers in the perinatal period.